Implementing and Managing a High-performance Enterprise Infrastructure with Nutanix on IBM Power Systems - Quintero, Dino; Barros, Ricardo; Gonzalez, Miguel; Díaz, Luis; Martinski, Slav; Jiménez, Gabriel; Moreno Valdivia, Ismael Franz; Munoz, Alan (IBM Redbooks, 2020)
This IBM® Redbooks® publication describes how to implement and manage a hyperconverged private cloud solution by using theoretical knowledge, hands-on exercises, and documenting the findings by way of sample scenarios. This book also is a guide about how to implement and manage a high-performance enterprise infrastructure and private cloud platform for big data, artificial intelligence, and transactional and analytics workloads on IBM Power Systems. This book use available documentation, hardware, and software resources to meet the following goals: Document the web-scale architecture that demonstrates the simple and agile nature of public clouds. Showcase the hyperconverged infrastructure to help cloud native applications mine cognitive analytics workloads. Conduct and document implementation case studies. Document guidelines to help provide an optimal system configuration, implementation, and management. This publication addresses topics for developers, IT architects, IT specialists, sellers, and anyone that wants to implement and manage a high-performance enterprise infrastructure and private cloud platform on IBM Power Systems. This book also provides documentation to transfer the how-to-skills to the technical teams, and solution guidance to the sales team. This book compliments any documentation that is available in IBM Knowledge Center, and aligns with the educational materials that are provided by the IBM Systems Software Education (SSE).
Online resource; Title from title page (viewed March 3, 2020)
Keywords: IBM Power systems; Computer networks -- Management; Information technology -- Management; Cloud computing; Réseaux d'ordinateurs; Gestion; Technologie de l'information; Gestion; Infonuagique; Information technology; Management; Computer networks; Management